Use virtual laboratories and information technology to teach chemistry in academic lyceums. - Badalboyeva Dilorom Sobirjon qizi (Peerian Journals Publishing, 2023)
This article explores the integration of virtual laboratories and information technology (it) in teaching chemistry within academic lyceums. It studies the benefits of using virtual laboratories, defines the methods of their implementation, presents the results of their application, discusses their consequences and provides conclusions and suggestions on the optimization of chemistry education
Keywords: Virtual laboratories; information technology; chemistry education